A Study of Metabolic Responses of R.Q, VO₂, and VCO₂ in Two Different Swimming Strokes - Pulen Das; Devendra Parmar; Akash Vishwakarma (Recent Trends in Sports, 2024)
This study investigates the metabolic responses, including Respiratory Quotient (R.Q), oxygen intake (VO₂), and carbon dioxide output (VCO₂), in freestyle and butterfly stroke swimmers. Understanding these responses is crucial for optimizing training and improving competitive performance. The study employed a comparative cross-sectional design involving 30 university-level swimmers (15 freestyle and 15 butterfly) who completed treadmill tests. Measurements of VO₂ and VCO₂ were taken using an S147 Rapid Response O₂/CO₂ Analyzer, with R.Q values calculated as the ratio of VCO₂ to VO₂. The findings showed that the two groups differed significantly, especially in terms of VO₂ and VCO₂ levels. Freestyle swimmers demonstrated higher VO₂ (3.50 L/min) compared to butterfly swimmers (3.18 L/min), reflecting greater muscle mass and anaerobic adaptations. Conversely, butterfly swimmers exhibited higher VCO₂ levels (2.69 L/min versus 2.35 L/min), indicating a greater reliance on aerobic metabolism. Nevertheless, no statistically significant distinction was discovered in R.Q values between the two strokes, suggesting that both groups utilize a mix of fat and carbohydrate metabolism. The findings emphasize the importance of tailored training strategies to match the specific metabolic demands of each stroke, potentially enhancing endurance, power, and overall performance. This study contributes to the broader understanding of sport-specific metabolic adaptations, providing valuable insights for coaches and athletes aiming to optimize training regimens.
Keywords: Metabolic responses; VCO₂; VO₂; aerobic capacity; butterfly stroke; competitive swimming; freestyle swimming; respiratory Quotient; training optimization; treadmill test